Enhancing and Extending the Meta-Analytic Comparison of Newer Genre Leadership Forms - Fuller, Bryan; Bajaba, Abdulah; Bajaba, Saleh (Frontiers in Psychology, 2022)
Interest in leadership research is growing, however, the rate of leadership learning is slowing down due to the proliferation of new leadership constructs. The objective of the present meta-analysis is to address the significant shortcomings in prior meta-analytic research on newer genre leadership forms by a) utilizing a substantially greater number of studies and observations than in previous meta-analyses and b) examining the meta-analytic correlations among the newer genre leadership forms. The results of the present study indicate that the newer genre leadership forms overlap to a greater degree than previously reported, while at the same time accounting for some degree of unique variance in the literature's most studied outcome variables; estimates of the relative contribution of each leadership form to the outcomes are provided, providing new insights into the distinctiveness of each leadership form. The findings suggest that pursuing an integrated theory and measure of newer genre leadership forms is a desirable future step for leadership research.